Papel da V-ATPase e de enzimas antioxidantes nos mecanismos de ajustamento ao estresse salino em feijão-de-corda (Vigna unguiculata (L.) Walp) - Oliveira, Luciana Maia Nogueira de (2007)
The accumulation of Na+ in the central vacuole represents an important mechanism for plants to cope with salt stress. V-ATPase plays a very important role in energizing transport across the vacuolar membrane. In many salt tolerant plants, V-ATPase is known to respond to NaCI stress with increased expression and enzyme activity [...]